L‐Asp is a useful tool in the purification of the ionotropic glutamate receptor A2 ligand‐binding domain. (17th April 2014) - Krintel, Christian; Frydenvang, Karla; Ceravalls de Rabassa, Anna; Kærn, Anne M.; Gajhede, Michael; Pickering, Darryl S.; Kastrup, Jette S.
<x xml:space="preserve">Abstract</x> In purification of the ionotropic glutamate receptor A2 (GluA2) ligand‐binding domain (LBD), l‐Glu‐supplemented buffers have previously been used for protein stabilization during the procedure. This sometimes hampers structural studies of low‐affinity ligands, because l‐Glu is difficult to displace, despite extensive dialysis. Here, we show that l‐Asp binds to full‐length GluA2 with low affinity (Ki = 0.63 mm) and to the GluA2 LBD with even lower affinity (Ki = 2.6 mm), and we use differential scanning fluorimetry to show that l‐Asp is able to stabilize the isolated GluA2 LBD. We also show that l‐Asp can replace l‐Glu during purification, providing both equal yields and purity of the resulting protein sample. Furthermore, we solved three structures of the GluA2 LBD in the presence of 7.5, 50 and 250 mm l‐Asp. Surprisingly, with 7.5 mm l‐Asp, the GluA2 LBD crystallized as a mixed dimer, with l‐Glu being present in one subunit, and neither l‐Asp nor l‐Glu being present in the other subunit. Thus, residual l‐Glu is retained from the expression medium. On the other hand, only l‐Asp was found at the binding site when 50 or 250 mm l‐Asp was used for crystallization. The binding mode observed for l‐Asp at the GluA2 LBD is very similar to that described for l‐Glu. Taking our findings together, we have shown that l‐Asp can be used instead of l‐Glu for ligand‐dependent stabilization of the GluA2 LBD during purification. This will enable structural studies of low‐affinity ligands for lead optimization in structure‐based drug design. Database Structural data are available in the Protein Data Bank under accession numbers 4O3B (7.5 mm l‐Asp), 4O3C (50 mm l‐Asp), and 4O3A (250 mm l‐Asp) Structured digital abstract GluA2 and GluA2 bind by x-ray crystallography (View interaction)